Selective Inhibition of Activated Stellate Cells and Protection from Carbon Tetrachloride-Induced Liver Injury in Rats by a New PPAR γ agonist KR62776 - Bae, Myung-Ae (2010)
Activated hepatic stellate cells (HSC) are the primary source of extracellular matrix proteins found in liver fibrosis/cirrhosis patients. Therefore, the prevention of HSC activation is an important strategy for treating severe liver injury. This study examined the effects of KR62776, a new peroxisome proliferator-activated receptor γ (PPARγ) agonist, on the rate of cell proliferation and expression of α-smooth muscle actin (α-SMA) in rat hepatic stellate HSC-T6 cells. In addition, its effects on the liver damage induced by carbon tetrachloride were investigated. KR62776 caused the apoptosis of activated HSC-T6 cells with the concomitant decrease in the α-smooth muscle actin levels in a time- and concentration-dependent manner. However, KR62776 did not cause the apoptosis of human HepG2 and rat McARH7777 hepatoma cells, suggesting that KR62776 has a specific effect on stellate cells. KR62776 increased the levels of Gadd45, p27, p21 and PPARγ proteins but decreased the cell cycle-related proteins, such as cdk2, cyclin B and cyclin D1. These changes were reversed by BADGE, a specific PPARγ antagonist, indicating that the effects of KR62776 are, at least in part, PPARγ-dependent. In addition, KR62776 administration showed some protection against carbon tetrachloride-induced hepatocellular damage in rats. Overall, these results suggest that KR62776 may have potential in the chemoprevention of liver fibrosis/cirrhosis.